Marine Biotechnology for sustainable futures - Dobretsov, Sergey (My University, 2019)
Marine Biotechnology or blue biotechnology is a sustainable usage of marine resources for the benefit of mankind. In this presentation the history of marine biotechnology and the main fields of the biotechnology will be presented. The emphasis will be given on anticancer and antifouling compounds from marine organisms. At the end of the presentation, the future research directions will be provided.
Keywords: Biotecnología marina; Biotechnology; Biofouling; Anticancer; Food processing